The role of phenolic compounds in metabolism and their antioxidant potential (Research, Society and Development, 2022)
The intake of fruits and vegetables rich in nutrients with bioactive properties is associated with the prevention of a range of chronic diseases such as cardiovascular diseases, diabetes, and cancer that originate from physiological disorders, which can be promoted by the accumulation of free radicals in the body. Several chemical compounds with bioactive functions are found in fruits and vegetables. Among these, phenolic compounds stand out for having high antioxidant capacity. These compounds originate from the secondary metabolism of plants, being essential for their growth and reproduction. In addition, they can be more expressed by plants under stress conditions, such as infections by microorganisms, lesions, severe climate changes, nutritional deficiency, among others. The highest concentrations of these phenols are found in fruit and vegetable skins, due to their potential use in protecting against UV rays, pathogens and predators. The search for new sources of natural and/or synthesized antioxidants has been growing due to the wide biological activity observed for these compounds, such as the inhibition of lipid oxidation and its action against the inactivation of free radicals. These compounds can be synthesized via the shikimate/phenylpropanoid pathway. It is believed that after consumption they are partially degraded in the small intestine, about 5 to 10%, and the rest in the large intestine. Here we review how the plant synthesizes phenolic compounds and their health effects, demonstrating the significant dietary activity of these compounds in metabolic processes.